Assessment of the healthy worker survivor effect in the relationship between psychosocial work-related factors and hypertension. Issue 6 (13th April 2019) - Massamba, Victoria Kubuta; Talbot, Denis; Milot, Alain; Pearce, Neil; Trudel, Xavier; Brisson, Chantal
Abstract : Objectives: The healthy worker survivor effect (HWSE) usually leads to underestimation of the effects of harmful occupational exposures. HWSE is characterised by the concomitance of three associations: (1) job status–subsequent exposure, (2) job status–disease and (3) previous exposure–job status. No study has reported the coexistence of these associations in the relationship between psychosocial work-related factors and health. We assessed if HWSE is present when measuring the effects of cumulative exposure to psychosocial work-related factors on the prevalence of hypertension in white-collar workers. Methods: Data were obtained from two timepoints (1991–1993 at baseline and 1999–2001 at follow-up) of a prospective cohort study. At baseline, the population was composed of 9188 white-collar employees (women: 49.9%) in Quebec City. Job strain as psychosocial work-related factor and blood pressure were measured using validated methods. Job status (retirees vs employees) at follow-up was self-reported. Multiple multilevel robust Poisson regressions were used to estimate prevalence ratios of hypertension and risk ratios of retirement separately by gender. We performed multiple imputations to control selection bias due to missing values. Results: Retirement eliminated the subsequent exposure to job strain de facto and was associated with the reduction in the prevalence of hypertension in younger (−33%) and older (−11%) men and in older women (−39%). Job strain was associated with job status in younger men and in women of any age. Conclusion: Data showed the presence of HWSE in younger men and older women given the coexistence of the three structural associations.